Faktor-faktor yang Mempengaruhi Minat Siswa dalam Kegiatan Ekstrakurikuler Tari di SMP Negeri 1 lubuk Alung - Zahra Nur Illahi; Marzam Marzam (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study aims to find out and describe the factors that affect students' interest in dance extracurricular activities at SMP Negeri 1 Lubuk Alung. This type of research is qualitative research. The main instrument in this study is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The types of data used in this study are primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews, and documentation. The steps to analyze data are data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that there are two factors that affect students' interest in dance extracurricular activities at SMP Negeri 1 Lubuk Alung, namely internally and externally. Internal factors include very good attention in dance extracurricular activities because students pay attention to the material when the activity is carried out, very good student attitudes because students always pray in participating in dance activities, poor ability because students do not understand dance movements taught by subject teachers, and motivation is also not good due to lack of motivation given by cultural arts teachers in attracting students' interest. External factors include teachers, advice and infrastructure, and learning methods. So it can be concluded that students' attention, attitude, ability, and motivation are very influential in dance extracurricular activities.